2020
DOI: 10.1002/ange.201915281
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial‐DNA‐Targeted IrIII‐Containing Metallohelices with Tunable Photodynamic Therapy Efficacy in Cancer Cells

Abstract: The development of DNA‐targeted photodynamic therapy (PDT) agents for cancer treatment has drawn substantial attention. Herein, the design and synthesis of dinuclear IrIII‐containing luminescent metallohelices with tunable PDT efficacy that target mitochondrial DNA in cancer cells are reported. The metallohelices are fabricated using dynamic imine‐coupling chemistry between aldehyde end‐capped fac‐Ir(ppy)3 handles and linear alkanediamine spacers, followed by reduction of the imine linkages. The length and odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 86 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…For example Duan linked two preorganised fac iridium( iii ) complexes, via reductive amination, to give the mesocate 6 . 22 There is thus an important balance to be struck between allowing the dynamic ligand exchange processes that furnish thermodynamic control in the self-assembly process, and the stability of the final system to hydrolysis or other substitution.…”
Section: Design Considerations For Metallohelices With Biomedical Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example Duan linked two preorganised fac iridium( iii ) complexes, via reductive amination, to give the mesocate 6 . 22 There is thus an important balance to be struck between allowing the dynamic ligand exchange processes that furnish thermodynamic control in the self-assembly process, and the stability of the final system to hydrolysis or other substitution.…”
Section: Design Considerations For Metallohelices With Biomedical Applicationsmentioning
confidence: 99%
“…Several in vitro studies with ‘naked’ DNA have demonstrated that various metallohelices can bind duplex DNA, since the first report by Lehn and co-workers. 51 Apparent binding constants have been measured for several compounds via ethidium bromide displacement, including P - 2 [Fe( ii ) analogue], 52 racemic - 3 -Co( iii ), 53 meso - 6 , 22 Δ- 9a , 36 ‡ In metallohelices such as 9 the metal coordination units have the opposite helical configuration to the bridging ligand strands, so the helical descriptors P and M are unsuitable, so absolute configuration descriptors for the metal centres Δ and Λ are used. Δ- 10 , 36 Δ- 12 , 47 Δ- 13 , 38 Δ- 15 ; 47 the measured K app lie in the range 10 6 to 10 8 , although we note the strong dependency on ionic strength.…”
Section: Examples Of Metallohelices With Biological Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…17 The activated photosensitizer will convey the energy of light to O 2 , generating ROS to kill tumor cells. 18 Despite PDT having been tested in the clinic for tumor treatment, an O 2 shortage in the tumor microenvironment and limited tissue-penetrating depth of light are two defects as reported. 19,20 Different from light-triggered PDT, SDT utilizes high tissue-penetrating ultrasound waves to irradiate sonosensitizers to trigger O 2 to subsequently generate ROS for tumor destruction.…”
mentioning
confidence: 99%